Volume 2: Combustion, Fuels and Emissions, Parts a and B 2012
DOI: 10.1115/gt2012-68804
|View full text |Cite
|
Sign up to set email alerts
|

Imprinted Effusion Modeling and Dynamic CD Calculation in Gas Turbine Combustors

Abstract: A practical computational fluid dynamics (CFD) approach to modeling effusion orifices in gas turbine combustor liners is proposed specifically when liner metal geometry is not included and conjugate heat transfer is not invoked. The focus is on eliminating effusion orifices from the model while maintaining the imprint of the orifices on the cold and hot sides of the liner wall. The imprinted boundaries serve as embedded mass flow inlets and outlets on both sides of the wall and maintain the integrity of the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Thus, the flow as well as the convective heat transfer inside the tube have to be modelled. For the flow an one dimensional momentum conservation equation based on a simple streamline theory can be used [3], [4]. The velocity at the hole exit is then calculated from pressure drop over the holes as follows…”
Section: Basic Ideamentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the flow as well as the convective heat transfer inside the tube have to be modelled. For the flow an one dimensional momentum conservation equation based on a simple streamline theory can be used [3], [4]. The velocity at the hole exit is then calculated from pressure drop over the holes as follows…”
Section: Basic Ideamentioning
confidence: 99%
“…Furthermore the results of an investigation of the influence of the grid size have been presented. In the work of Rida et al (2012) [4] the authors reported an alternative method to the addition of source terms, hence represented by imprinted effusion modelling which consists in defining cold and hot sides of the effusion orifice with outlet and inlet boundary conditions but at adiabatic conditions only. The mass flow rate is calculated locally starting from the pressure drop and a correlation-based calculation of a discharge coefficient c D .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one, less expensive, leads to average solutions when the second gives access to instantaneous solutions and thus, better predicts the mixing and the turbulence flame interaction, which is more desirable in combustor simulations. To represent the liners, various modelling strategies have been used in the literature [13][14][15][16][17][18]. To distinguish these models and relate them to corresponding mesh resolution constraints, it is useful to introduce the aperture-to-mesh ratio:…”
Section: Introductionmentioning
confidence: 99%
“…Another innovative solution was developed by Rida et al [11], which reported that up to a million cells is required for a single hole to reach the mesh independence for an accurate prediction of the flow structures within the perforation. According to the authors, a feasible method, alternative to the addition of source terms, is hence represented by imprinted effusion modeling, which consists in coupling cold and hot sides of the effusion orifice with an outlet and inlet boundary condition, without meshing the hole.…”
Section: Introductionmentioning
confidence: 99%